Correlation Analysis of the Microbiome and Immune Function in the Lung-Gut Axis of Critically Ill Patients in the ICU - Liu, Bin; Yu, Ying; Zhao, Min; Xiao, Kun; Yan, Peng; Duan, Zhimei; Wang, Kaifei; Zhao, Na; Cao, Jiabao; Wang, Jun; Xie, Lixin (Frontiers in Medicine, 2022)
Objective: Critical illnesses in the intensive care unit (ICU) has been a global burden. We aimed to determine the correlation between the lung and gut in critically ill patients to find novel evidence of the lung-gut axis, which may be a new treatment for critically ill patients in the ICU. Methods: We collected bronchoalveolar lavage specimens and fecal samples of 31 critically ill patients within 24 hours after admission. Metagenomics was used to detect lung and intestinal samples. Immune cells were detected by flow cytometry. Results: There are 86 common species in both lung and gut. The abundance of Enterococcus faecium is high in both the lung and gut of critically ill patients in the respiratory intensive care unit (RICU). Corynebacterium striatum in the lung and gut is correlated with different immune cells. In addition, Corynebacterium striatum in the lung and gut might share the same source, supporting the concept of a gut-lung axis in humans. Conclusions: The microbiome in the lung and gut showed a correlation to some extent, and Corynebacterium striatum in the lung and gut might share the same source. In addition, the microbiome showed a correlation with immunity, indicating a potential therapeutic target in critically ill patients. The lung-gut axis might play an important role in patients with critical illness in the RICU.